2013
DOI: 10.1542/peds.2013-1816
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Conventional Medicine Use Among Youth With Recurrent Headaches

Abstract: OBJECTIVE: To identify prevalence and patterns of complementary and alternative medicine (CAM) use among youth with recurrent headaches (HA) and evaluate associations with co-occurring health problems and limitations as well as with the use and expenditures for conventional medical care. METHODS: Variables were constructed for youth aged 10 to 17 by using linked data from the 2007 National Health Interview Survey and the 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 57 publications
3
44
0
Order By: Relevance
“…Previous research suggests that among headache patients, use of mind-body therapies is second only to dietary supplements. 48 We were not surprised that participants reported using magnesium and riboflavin since these are adjunctive treatments recommended by many neurologists and other physicians for migraine headaches in adults; 49, 50 however, it was surprising that none of the adolescents in our sample reported using other commonly used herbs and supplements for headache such as butterbur, feverfew and Coenzyme Q10.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous research suggests that among headache patients, use of mind-body therapies is second only to dietary supplements. 48 We were not surprised that participants reported using magnesium and riboflavin since these are adjunctive treatments recommended by many neurologists and other physicians for migraine headaches in adults; 49, 50 however, it was surprising that none of the adolescents in our sample reported using other commonly used herbs and supplements for headache such as butterbur, feverfew and Coenzyme Q10.…”
Section: Discussionmentioning
confidence: 85%
“…1, 2 Tension-type headache (TTH) is the most common with prevalence rates ranging from 10 to 25 percent in school-aged children. 3 Migraine headaches are somewhat less common with prevalence ranging from about 3 percent in younger school-aged children to nearly 20 percent in older adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…While findings varied for level of income [58, 70] and level of education, [70, 72, 73] this patient group were more likely to be older [70, 72], female [20], have a higher rate of comorbid conditions [58, 70, 76] and a higher rate of previous medical visits [20, 58, 70] when compared to the non-user group. Overall, this group were reported to have a higher level of headache chronicity or headache disability than non-users [20, 54, 58, 70, 72, 77].…”
Section: Resultsmentioning
confidence: 99%
“…13 In a recent study looking at CAM use in children with recurrent headaches, children who experience headaches are 2.1 times more likely to use CAM. 14 Other studies have found that CAM use was higher in those with a chronic medical condition such as cancer, juvenile idiopathic arthritis and sickle cell anemia compared to the general population. 15 …”
Section: Introductionmentioning
confidence: 96%